Nondestructive test for quality control in laboratory-scale fabrication of laminated composites using programmable portable ultrasonic - Yusuf Giri Wijaya; Suprijanto; Damar Rastri Adhika; Rhakamerta Hijazi; Abian Nurrohmad (International Journal of Lightweight Materials and Manufacture)
Laminated composites are the most frequently used component materials in manufacturing unmanned aerial vehicles (UAVs) in research centers or start-up industries. On a laboratory scale, laminated composites are fabricated by relying on technicians' skills due to the involvement of manual processes. Nondestructive testing (NDT) is needed to guarantee the structural integrity of the final product of laminated composites. The work proposes a programmable portable ultrasonic for nondestructive testing (NDT) to detect a potential defect due to foreign object contamination of fabrication layers of laminate composite. The proposed programmable NDT system is built using open-board devices; therefore, it could be developed cost-effectively compared to a commercial NDT system. The proposed NDT can measure and analyze a pattern of A-scan signal as a function of foreign object contamination material. Based on a C-scan image, the proposed NDT system could also be programmed to detect the size area of potential defects due to foreign object contamination. Two types of specimens, carbon fiber-reinforced polymer (CFRP) and glass fiber-reinforced polymer (GFRP), were tested to evaluate the performance of the developed NDT system. Testing aims to identify artificial defects intentionally placed within these specimens. The proposed portable ultrasonic NDT effectively detects CFRP and GFRP defects on A-mode and C-scan images. Therefore, the proposed portable ultrasonic NDT is an affordable system that can be developed in a laboratory workshop for quality control in laboratory-scale fabrication of laminated composites.